THE EFFECT OF CONTECT, INPUT AND PROCESS IN ACHIEVING INTERPROFESSIONAL COMMUNICATION AND TEAMWORK COMPETENCES - Nurul Fauziah; Mora Claramita; Gandes Retno Rahayu (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Interprofessional Education (IPE) is a process occurs when students from two or more professions learn about and from each other to enable effective collaboration and improve health outcomes. Faculty initiated the IPE program called Community and Family Health Care - interprofessional Education (CFHC-IPE) that began in 2013 with the aim to build the capacity of community, family medicine and interprofesional. This study aims to evaluate the effect of context, input and process towards the achievement of interprofessional competences.Method: This study was a qualitative research design using a case study evaluation Context-Input-Process-Product (CIPP). Respondents of this study are five-IPE CFHC managers, three heads of study program, 10 lecturers and 35 students from PSPD, PSIK and PSGK. Data collected through FGD, in-depth interviews and document analysis. FGD and in-depth interviews conducted using an interview guide while document analysis carried out on the grand design CFHC-IPE. Results: Context evaluation shows that the needs assessment has not been carried out. Input evaluation shows that the preparation of the grand design CFHC-IPE is not align and debriefing facilitators need to be added. There were gaps in the implementation of learning activities and assessment and program monitoring was inadequate. IPE competencies in the first year on the student of 2014 were not achieved. Conclusion: Inter-professional communication and teamwork competence on student of class 2014 at CFHC-IPE program in the first year was not achieved and influenced by the weaknesses in the content, inputs and processes aspects.